(untitled) (Honolulu, 2001)
Silence to the Light commemorates the 60th anniversary of Japan's attack on Pearl Harbor and the 70th anniversary of the outbreak of World War 2 in Asia, in 1931. Through powerful short stories, poetry, manga, and memoirs, events such as the Manchurain Incident, the Rape of Nanking, the Battle of Okinawa, and the atomic bombing of Hiroshima and Nagasaki are presented in a variety of voices, all deeply affecting. Photographs, letters and testimonials add further detail to these stories of ordinary people caught up in a war's madness.
Keywords: Japan,Nhật Bản; History war,Lịch sử chiến tranh